The Victim–Perpetrator Overlap in Financial Cybercrime: Evidence and Reflection on the Overlap of Youth's On-Line Victimization and Perpetration. Issue 5 (3rd May 2016) - Kerstens, Joyce; Jansen, Jurjen
ABSTRACT: This study investigates the victim–perpetrator overlap for financial cybercrimes: auction fraud, virtual theft, and identity fraud. Conducting a cross-sectional study among Dutch youth aged 10 to 18 ( N = 6, 299), the results show that the victim–perpetrator overlap for financial cybercrime is considerable. Perpetration is strongly motivated by retaliation. The findings from the multinomial regression model show that low self-control and high on-line disinhibition are positively and significantly associated with victimization and perpetration. The findings demonstrate that the overlap between financial cybercrime victimization and perpetration is partially explained by retaliation, low self-control and on-line disinhibition, suggesting that state-dependency and individual heterogeneity explanations should be supplemented by explanations funded in the dynamics of the on-line environment.